Open reduction and internal fixation of fracture femur in a patient with severe ankylosing spondylitis utilizing continuous caudal epidural anaesthesia - Thakur, Aman; Sood, Priyanka; Rana, Shelly; Kumar, Sudarshan (International Journal of Research in Medical Sciences, 2017)
We describe a patient with severe ankylosing spondylitis scheduled to undergo open reduction and internal fixation. We emphasise on alternative anaesthetic management in view of non-availability of fiberoptic bronchoscope and unwillingness of patient to go to higher centre. Regional (continuous caudal epidural) anesthesia has been used as technique of choice.